The Tamil Language as More Central than Even the Gods The Movie THIRUVILAYADAL (IN 1965) Is an Outlier as a Devotional Film - Gopalkrishnan, Sreeram; Sreeram, Lekshmi (Journal for Religion, Film and Media, 2023)
The narrow genre of devotional films in India follows a regular template – a combinationof theophanic interventions, bhakti (devotional) worship and didactic narratives.Thiruvilayadal (The Divine Play, Akkamappettai Paramasivan Nagarajan, IN 1965), afilm in Tamil (a language spoken across South and East Asia by a large diaspora), waslong considered a devotional movie that celebrated the God Shiva. However, a closeanalysis shows that the movie subverts the darshan concept (viewing) in a Hindu devotionalfilm. Though it may appear to be a film about Puranic (mythic) Hindu gods,the subtle subtext reduces heavenly entities to supplicatory positions in relation toa cornerstone of identity in the post-independence Dravidianist Tamil State – Tamillanguage. This understanding of Thiruvilayadal is all the more relevant in light of theincreasing rigidity of Hindu religious beliefs in contemporary India.